Business Intelligence, Corporate Governance and Economic Performance: Evidence from Transcorp Conglomerate for the period 2012 - 2021 - Wahua, Lawrence; Mkombo, Alfred Lameck; Okolobi, Augustine Nwaonye; Dioha, Abuah Ifeanyichukwu Rosemary; Attipoe, Julius K. A. M. (Journal of Social Sciences and Management Studies, 2023)
Investment in business intelligence keeps soaring as businesses strive to achieve timely data-driven decisions. This empirical study desired to quantitatively establish if the huge investment in business intelligence translates to increased profitability; and if its interaction with corporate governance variables like board emoluments and meetings lead to significant increase in profitability. Anchoring on economic theory with secondary data from Transcorp Conglomerate from 2012 – 2021, the research established that: excessive investment in business intelligence leads to significant decrease in profitability; high board emoluments and increased number of meetings have significant negative effects on profitability; bank size have significant positive effect on profitability; the interactions of business intelligence and board emoluments as well as the interactions of business intelligence and board meetings have significant positive effects on profitability; and the interaction of business intelligence, board emoluments and board meetings has significant negative effect on profitability. The study established the relevance of economic theory on business intelligence and governance study; and recommends that firms in general should optimise